2005
DOI: 10.1016/j.jweia.2005.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Drag coefficients and Strouhal numbers of a port crane boom girder section

Abstract: This work reports the drag coefficients (C d) for three wind directions measured in low turbulence flow and in turbulent flow with characteristics of the atmospheric boundary layer wind, and the Strouhal numbers (St) of an approximately trapezoidal flanged section, used in the boom girder of a 100 m high port crane. These experimental results were obtained at the Boundary Layer Wind Tunnel of the Dept. Aeronautica at the Universidad Nacional de La Plata, in the range of Reynolds numbers between 30,000 and 180,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The aerodynamic force due to the wind action is given by the product of the kinetic pressure (variable with the height) with the section diameter and the force coefficient [23]. The main parameters are:…”
Section: Study the Chimney Subject To Equivalent Static Actionmentioning
confidence: 99%
“…The aerodynamic force due to the wind action is given by the product of the kinetic pressure (variable with the height) with the section diameter and the force coefficient [23]. The main parameters are:…”
Section: Study the Chimney Subject To Equivalent Static Actionmentioning
confidence: 99%
“…doi:10. /j.jweia.2007 precautions for withstanding the wind loads (Scarabino et al, 2005). In general, a draft design is usually made by estimating the wind load of simple-shaped large structures, but the actual wind load is more or less different from prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental effects were not taken into account and there was no special condition of exposure or shelter (Eden et al, 1981;Voisin et al, 2004). Scarabino et al (2005) reported the drag coefficients and Strouhal numbers of a port crane boom girder in smooth flow and in an atmospheric wind flow with large turbulence intensity. They mentioned that the approximately two-dimensional geometry and the low natural frequencies of the long crane booms would cause dangerous dynamic wind loads through the vortex shedding mechanism even at low-speed winds.…”
Section: Introductionmentioning
confidence: 99%
“…Static and dynamic wind loads are important design parameters to consider for taking the necessary precautions for withstanding such wind loads [1]. In general, a draft design is made by roughly estimating the wind load on simple-shaped structures.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental effects were not taken into account, and there was no special consideration on exposure or shelter [2,3]. Scarabino et al [1] measured the drag coefficients and Strouhal numbers of a boom girder section of a port crane in smooth flow and in an atmospheric wind with large turbulence intensity. They mentioned that the approximately two-dimensional geometry and the low natural frequencies of the long crane booms would cause dangerous dynamic loads through the vortex shedding mechanism even at low-speed winds.…”
Section: Introductionmentioning
confidence: 99%